Synthesis of multicyclic β-Lactam derivatives via solid-phase- generated ketenes - Mendez, Luciana (2010)
An efficient approach for the solid-phase synthesis of multicyclic â-lactam derivatives is described. The key step is the cycloaddition reaction between an immobilized ketene and different cyclic imines to afford the corresponding benzofused carbacepham derivatives in high yield for the overall synthetic sequence.